Longitudinal evaluation of hepatic lipid deposition and composition in ob/ob and ob/+ control mice. (28th January 2013) - Ye, Qiong; Danzer, Carsten Friedrich; Fuchs, Alexander; Vats, Divya; Wolfrum, Christian; Rudin, Markus
<x xml:space="preserve">Abstract</x> Obesity is associated with insulin resistance (IR) and hepatosteatosis. Understanding the link between IR and hepatosteatosis could be relevant to chronic clinical outcomes. The objective of this study was to quantitatively assess lipid deposition (fractional lipid mass, fLM) and composition (fraction of polyunsaturated lipids, fPUL and mean chain length, MCL) in livers of ob/ob mice, a genetic model of obesity and mild diabetes, and ob/+ heterozygous control animals in a noninvasive manner using 1H‐MRS at 9.4T. For accurate quantification, intensity values were corrected for differences in T2 values while T1 effects were considered minimal due to the long TR values used. Values of fLM, fPUL and MCL were derived from T2‐corrected signal intensities of lipids and water resonance. Hepatic lipid signals were compared with fasted plasma insulin, glucose and lipid levels. Statistically significant correlations between fPUL and fasting plasma insulin/glucose levels were found in adolescent ob/ob mice. A similar correlation was found between fLM and fasting plasma insulin levels; however, the correlation between fLM and fasting plasma glucose levels was less obvious in adolescent ob/ob mice. These correlations were lost in adult ob/ob mice. The study showed that in adolescent ob/ob mice, there was an obvious link between lipid deposition/composition in the liver and plasma insulin/glucose levels. This correlation was lost in adult animals, probably due to the limited lipid storage capacity of the liver. Copyright © 2013 John Wiley & Sons, Ltd.